EFFECT OF AGING ON THE AESTHETIC AND DECORATIVE FEATURES OF THE INNOVATIVE SALIXDUO PRODUCT FINISHED WITH ACRYLIC AND POLYURETHANE LACQUERS - Lis, Barbara; Krystofiak, Tomasz; Sumionka, Mikołaj; Danecki, Leszek; Waliszewska, Bogusława (Innovation in Woodworking Industry and Engineering design, 2024)
An innovative research material called "Salixduo" was developed and patented as part of an ongoing shrub willow wood rods project. With a view to the final use of this product, it was decided to conduct aging tests of the finished product. Two acrylic and one polyurethane lacquer were selected for testing. Their application by pneumatic spray in the form of two coatings was carried out in the technology laboratory of a leading manufacturer of lacquer products. After 28 days of seasoning under laboratory conditions (temperature 20±5°C and relative humidity 65±5%), the parts were cut into samples for aging tests. The coatings were then exposed to UV radiation, UV+IR radiation, and varying humidity and temperature acc. to the AMK procedure as a function of time. The parameters evaluated were appearance, color, and gloss. Gloss testing of lacquer coatings was performed by a photoelectric method using a TESTAN DT-G268 gloss meter according to PN-EN ISO 2813:2001. Measurements were made at three angles of incidence of light at ten randomly selected locations in the direction along and across each sample. The color determination was determined with a DT-145 colorimeter, using a CIELab measurement system equipped with a daylight illuminator and 45º/0° directional measurement geometry. Ten measurements were taken on each sample before and after application of varnish. They were carried out always in the same places, thanks to the marked measuring areas. Based on the results of the tests, the most significant effect on changes in color and degree of gloss was found after exposure to UV, followed by UV+IR.